ROLE OF RELIGIOUS ORIENTATION AND MENTAL HEALTH ON CRITICAL THINKING AMONG ACADEMICIANS - Yameen, Ayesha; Iftikhar, Lubna; Javed, Ayesha (PEOPLE: International Journal of Social Sciences, 2019)
The present study investigated the role of religious orientation (intrinsic and extrinsic) and mental health (psychological well-being and psychological distress) on critical thinking among academicians. Moreover, the role of various variables such as difference in gender were also explored as part of this study. Scales used in this study were Age Universal Religious Orientation Scale (AUROS), Mental Health Inventory (MHI), and Watson-Glaser Critical Thinking Appraisal (WGCTA-S). Data was gathered by convenient sampling of 150 academicians (75 males, 75 females) within the age limit of 25-40 years from public and private universities in Islamabad. Data was tabulated and analyzed using SPSS. The results suggested that extrinsic religious orientation and psychological distress are positively correlated whereas extrinsic religious orientation and critical thinking are negatively correlated. The results also concluded that intrinsic religious orientation, psychological well-being and critical thinking are positively correlated. Results concluded that male professionals scored higher on religious orientation, mental health index and critical thinking as compared to their female counterparts (N=150).